Ensemble source apportionment of air pollutants and carbon dioxide based on online measurements. (10th October 2022) - Wang, Zhenyu; Yu, Haofei; Liang, Weiqing; Wang, Feng; Wang, Gen; Chen, Da; Wang, Weichao; Zhao, Huan; Feng, Yinchang; Shi, Zongbo; Shi, Guoliang
Abstract: Air pollution and climate change have attracted worldwide attention due to their significant threats to human health and the environment. To maximize the co-benefits of clean air policies on greenhouse gas emissions and vice versa, it is imperative to coordinate emission control measures for air pollutants and carbon dioxide (CO2 ). To do this, we first need to better quantify the impacts of different sources to air pollutants and CO2 at once. Based on a 2-year observation of fine particulate matter (PM2.5 ), gaseous pollutants (including sulfur dioxide (SO2 ), nitrogen oxides (NOx ), initial volatile organic compounds (In–VOCs)), as well as CO2, we apportioned the sources of criteria air pollutants and CO2 simultaneously. We then developed a new source apportionment method to quantitatively determine the relative impacts of different emission sources on (1) gaseous pollutants ensemble (SO2 -NOx -In-VOCs) and (2) PM2.5 and CO2 ensemble (PM2.5 -CO2 ). The results demonstrate that vehicle exhaust (35%), industrial emissions (31%), biomass burning (18%), and coal combustion (16%) were the main control targets for the SO2 -NOx -In-VOCs ensemble, and they were also the dominant contributors to PM2.5 -CO2 ensemble with similar contribution rates. Not surprisingly, the source impacts are substantially different for the two studied ensembles to those of individual air pollutant alone. This study provides a new source apportionment method to deliver scientific evidence for developing a coordinated strategy to maximize the benefits of clean air and carbon policies to air quality and the climate. Graphical abstract: Image 1 Highlights: Concentrations and sources of PM2.5, gaseous pollutants and CO2 were analyzed. Developed weighted average method that can quantify ensemble source impacts. Reduce combustion source emissions benefit control of gaseous pollutants and PM2.5 -CO2 .